From Stress to Sick(le) and Back Again-Oxidative/Antioxidant Mechanisms, Genetic Modulation, and Cerebrovascular Disease in Children with Sickle Cell Anemia - Marisa Silva; Paula Faustino (MDPI AG, 2023)
Sickle cell anemia (SCA) is a genetic disease caused by the homozygosity of the HBB:c.20A>T mutation, which results in the production of hemoglobin S (HbS). In hypoxic conditions, HbS suffers autoxidation and polymerizes inside red blood cells, altering their morphology into a sickle shape, with increased rigidity and fragility. This triggers complex pathophysiological mechanisms, including inflammation, cell adhesion, oxidative stress, and vaso-occlusion, along with metabolic alterations and endocrine complications. SCA is phenotypically heterogeneous due to the modulation of both environmental and genetic factors. Pediatric cerebrovascular disease (CVD), namely ischemic stroke and silent cerebral infarctions, is one of the most impactful manifestations. In this review, we highlight the role of oxidative stress in the pathophysiology of pediatric CVD. Since oxidative stress is an interdependent mechanism in vasculopathy, occurring alongside (or as result of) endothelial dysfunction, cell adhesion, inflammation, chronic hemolysis, ischemia-reperfusion injury, and vaso-occlusion, a brief overview of the main mechanisms involved is included. Moreover, the genetic modulation of CVD in SCA is discussed. The knowledge of the intricate network of altered mechanisms in SCA, and how it is affected by different genetic factors, is fundamental for the identification of potential therapeutic targets, drug development, and patient-specific treatment alternatives.